A pilot survey on ‘Muslim – friendly’ event management standards in Malaysia and its acceptance among Malaysian practitioners - Zainan Nazri, Nurul Jannah; Fatah Yasin, Raudlotul Firdaus (2018)
Event management is a fast-paced, varied, and highly employable field. Even in times of economic recession, events remain invaluable to companies as an assured way to build brand reputation, drive consumer confidence and give people experiences to remember. The International Organization of Standardization has realized the importance of providing standards and guidelines for event management, which ultimately led to the existence of event management standard; “ISO 20121: 2012 Event sustainability management systems - Requirements with guidance for using it in 2012". Indeed, it was started earlier by the British Standard for "'BS8901 Event Management Standard" in 2005. However, the previous mentioned standards are not fully complied with the Shariah. The present study focuses on developing a sustainable 'Muslim friendly' standards of event management in Malaysia as a Muslim-majority country.